Prática de gestão de projetos em uma entidade filantrópica: um desafio necessário - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The entities that constitute the Third Sector, that is, the non-profit, have been experiencing a great difficulty regarding their sustainability, seeking to provide services to the community with quality, but without sufficient financial resources for such demand. The objective of this work is to understand how project management happens in the Association of Parents and Friends of Exceptional People of Santana do Livramento, taking into consideration the financial resources. For such study, a bibliographical review and a case study were conducted through interviews conducted at the Institution and Public Authorities. One can observe the difficulty that the entity has in the collection of public financial resources, which generates a loss in the service offered free of charge to users.
Practice of project management in a philanthropic entity: a challenge required
Keywords: Terceiro setor; Gestão de projetos; Entidade filantrópica; Recursos financeiros; Third sector; Project management; Philanthropic entity; Financial resources; CNPQ::CIENCIAS SOCIAIS APLICADAS